An Account of Amyloid Oligomers: Facts and Figures Obtained from Experiments and Simulations. (21st March 2016) - Nagel‐Steger, Luitgard; Owen, Michael C.; Strodel, Birgit
Abstract: The deposition of amyloid in brain tissue in the context of neurodegenerative diseases involves the formation of intermediate species—termed oligomers—of lower molecular mass and with structures that deviate from those of mature amyloid fibrils. Because these oligomers are thought to be primarily responsible for the subsequent disease pathogenesis, the elucidation of their structure is of enormous interest. Nevertheless, because of the high aggregation propensity and the polydispersity of oligomeric species formed by the proteins or peptides in question, the preparation of appropriate samples for high‐resolution structural methods has proven to be rather difficult. This is why theoretical approaches have been of particular importance in gaining insights into possible oligomeric structures for some time. Only recently has it been possible to achieve some progress with regard to the experimentally based structural characterization of defined oligomeric species. Here we discuss how theory and experiment are used to determine oligomer structures and what can be done to improve the integration of the two disciplines. Abstract : Fatal protein–protein interactions that result in the formation of amyloid fibrils are common features of many neurodegenerative disorders, such as Alzheimer's disease. Prefibrillar amyloid oligomers are thought to be key players in amyloid cytotoxicity. Therefore, the elucidation of their structures is of enormous interest.